2020
DOI: 10.9770/jesi.2020.8.2(55)
|View full text |Cite
|
Sign up to set email alerts
|

New Approach to determining the economic potential of rural area on the example of the South Bohemian region of The Czech Republic

Abstract: The paper discusses a new approach to determining the economic potential of rural area on the example of the region of South Bohemia in the Czech Republic. The approach is based on a comprehensive economic model, consisting of four sub-models (SM). Such aggregate model is used as the basis for the analysis of regional economic potential. The SMs were defined by the Progressivity Index of the Economic Structure, Trend of the Economic Structure Index, Business Activity Rate and Recreation and Tourism Index. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…Shrinking population size and declining economic power lead to a decrease in public transport services and a decline in social and cultural activities in rural areas. The innovativeness of Czech small rural enterprises is also affected by poor institutional infrastructure, limited availability of public services and the withdrawal of services that can facilitate the work of businesses, such as post offices (Pártlová et al, 2020b). Moreover, in addition to geographical rural disadvantages, business size also influences the intensity of innovation activities.…”
Section: Small Rural Enterprise Innovation In the Czech Republicmentioning
confidence: 99%
“…Shrinking population size and declining economic power lead to a decrease in public transport services and a decline in social and cultural activities in rural areas. The innovativeness of Czech small rural enterprises is also affected by poor institutional infrastructure, limited availability of public services and the withdrawal of services that can facilitate the work of businesses, such as post offices (Pártlová et al, 2020b). Moreover, in addition to geographical rural disadvantages, business size also influences the intensity of innovation activities.…”
Section: Small Rural Enterprise Innovation In the Czech Republicmentioning
confidence: 99%
“…The author further states that an important factor that influences the potential of rural areas is the construction of a sufficient infrastructure network and ensuring a quality connection of urban agglomerations with rural regions. Li et al (2019) and Pártlová (2020b) add that it is necessary to strengthen the functional links or establish functional information flows by means of creating networks between towns and rural areas on the basis of activating the human potential that actually exists there. The assumption is that a newly conceived economic, business, and social potential can be built based on the multidimensional networking of both types of agglomerations.…”
Section: Petra Pártlovámentioning
confidence: 99%
“…In the last decade, the European Community, including a number of national governments of the EU member states, has become aware of the negative development of rural areas and the need to handle this problem (Pártlová et al, 2020b). As the authors state, it is indisputable that rural areas are highly distinct and diversified; their specificity determines the need for new or specialized theoretical knowledge, methodology for designing a rural area development strategy based on actual, up-to-date data regarding the economic potential of the area or locality and resulting implementation of methodologies in user practice by this real knowledge (Pártlová et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the article (Pártlová P. et al, 2020) is to develop a new approach to determining the economic potential of rural areas on the example of the South Bohemian region in the Czech Republic. The basis for the analysis of the economic potential of the region, the authors identified a complex model consisting of four submodels.…”
Section: Literature Reviewmentioning
confidence: 99%